The Impair Iron Metabolism in Acute Pancreatitis - Yu. P. Orlov; V. T. Dolgikh; V. N. Lukach; A. V. Yershov; T. V. Pritykina (Общая реаниматология, 2010)
Objective: to develop a method for preventing hepatic failure. Subjects and methods: Sixty-three patients with a complicated course of acute pancreatitis, admitted to the intensive care unit, were examined and treated. Thirty-one patients received standard intensive therapy and 32 patients had an intensive treatment program comprising deferoxamine in a dose of 6—12 mg/kg without octreotide. The activities of AsAT and AlAT and the levels of total bilirubin and its fractions, ferritin, and free hemoglobin were determined in plasma three times (on admission, 1 and 3 days later); the activities of superoxide dismutase and catalase were also examined. The severity of endotoxemia was assessed by the levels of low- and medium-molecular-weight substances in plasma and on red blood cells. Results. Incorporation of deferoxamine into the intensive therapy program for severe acute pancreatitis could reduce the incidence of hepatopathy and decrease that of pancreatogenic sepsis and retroperitoneal phlegmon by 3 times and mortality rate by 19.6%. Conclusion. The use of deferoxamine in the intensive therapy program is pathogenetically warranted because, by binding excess iron ions in plasma, the agent prevents the development of occasionally fatal complications of acute pancreatitis.